Competency Requirement for Effective Property Management in Malaysia - Logavani Balakrishnan; Ishak, Mohd Hafizal (International Journal of Sustainable Construction Engineering and Technology, 2022)
A knowledgeable and skilled property manager will add value to the assets and increase customer satisfaction. Weaknesses in this aspect will affect the efficiency of a property manager in managing complex issues in real estate. This study focuses on competency requirements for effective property management in Malaysia. The objectives are to determine competency requirements for property manager in Malaysia and to analyse the relationship between competency requirements with practices of property management. The quantitative method was used through the questionnaire with 81 sheets distributed to the property manager. Descriptive statistics and correlation analysis were used for analysing the data. Skills segment and duties and responsibility were analysed with improved knowledge and skills, and the needs for essential skills variables. The result shows that strong communication skills and tenant control are the most important skills for a property manager. On the other hand, paying maintenance costs and collecting rent and property fees are the highest duties and responsibilities of the property manager. Based on the correlation analysis between competency requirement and practice, it was found that tenant control has the highest correlation with saved money variables in the essential skills segment.